Emotional Features of Women as Mothers - Kryzhanovska, Zoreslava (Psychological Prospects Journal, 2014)
This paper presents the results of theoretical and empirical studies of the necessity of emotional support of women in the implementation of the parent role. Studying the problem made it possible to determine the complex structure of the parent role in a woman’s life, its importance for the development of the child, and the multiplicity of cultural and individual variants influencing the woman. The fundemental necessity of carrying out research into emotional characteristics of women in the implementation of the maternal role is paramount. The aim of the first phase of the study was the formation of groups to be investigated : the first included mothers on the level of «emotional burnout» which was low to moderately average, while the second was rated – with high scores on this basis. The differences in terms of «emotional burnout» of the two studied groups were found to be at a statistically significant level. The author suggests that these results are due to the process of development of a woman in her role as a mother. The study of the emotional characteristics of women in the implementation of their maternal role showed that mothers who are not experiencing «emotional burnout» in the upbringing of their child were characterized by their active role in child rearing and a positive attitude. The last stage of the diagnostic program was aimed at studying the characteristics of the type of relationships in the two studied groups. Comparison and correlation of the results shows that there were differences in the groups studied: for women with emotional experiences which are of a positive nature, the interaction with the child was mostly harmonious. These women were positively disposed to her child and sensitive to her needs, creative in her relations with the child and did not limit the child’s independence and activity. Women with increased rates of emotional exhaustion showed difficulties in interaction with the child: they provided insufficiently to developing a sense of acceptance and love, misunderstood the child’s desires, and did not adequately assess the child’s capabilities. Summarizing the results of the research, it is worth noting that the performance of a woman as a parent is dependent on both positive and negative emotional variables which have a direct impact on her interaction with the child.
Keywords: woman, motherhood, parent functions «emotional burnout» type of relationship with the child.